Sistem Pakar Diagnosa Penyakit Pada Kucing Anggora Menggunakan Metode Fuzzy Mamdani Berbasis Website - Nur Aynun Siregar; Rizalul Akram; Nurul Fadillah (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
Cats are the most popular mammals for many people, such as the Angora cat. Cat lovers don't look at age, most of these cats are liked by all people so it's not uncommon for cats to be found everywhere. The Angora cat has a beautiful physique with fur and a cute face. So it's not uncommon for the Angora cat to become the most preferred charmer of hearts. This hobby of keeping cats is not only seen from their stature but must be accompanied by their health. Some of the diseases that are often suffered by Angora cats include Feline Calicivirus, Helminthiasus, Dermatopytosis, Conjunctivitis, and Toxoplasmosis. This expert system is used by carers to diagnose early disease in Angora cats based on the symptoms experienced by cats and to help provide information about the cat's disease. Research data using laboratory tests, interviews and documentation were then processed using the Fuzzy Mamdani method and research design with UML which was designed in a use case diagram model to describe system activity. The stages are forming the Fuzzy Mamdani set, determining the rules, and defuzzification. The test results with 46 symptoms from 5 types of disease with an accuracy value of this system is 90.90%. The result of this research is that the system can help Anggora lovers from an early age to find out what are the symptoms of various types of cat diseases, as well as solutions to overcome them and can consult a doctor before proceeding to a more advanced stage.